Redefining Humanitarianism: Proposing a New Scale for Measurement - MERSNI , Soumaya; BAKINI , Fatma (Revue Internationale des Sciences de Gestion, 2024)
The world is currently grappling with crisis-stricken contexts that profoundly affect people's lives, creating urgent needs for humanitarian interventions to help vulnerable populations survive. Humanitarianism, traditionally applied in times of crisis, is now evolving into a broader approach that integrates humanitarianism in daily activities. This shift aims to provide continuous support to people in need and alleviate the difficult conditions they face. At its core, humanitarianism represents the compassionate response to the suffering of strangers. While this variable has been in existence since time immemorial, it remains complex because it is poorly defined and lacks measurement. The purpose of this study is to develop and validate a new scale for measuring humanitarianism, designed to reflect contemporary realities and the evolving approach to humanitarianism. This scale is constructed following the methodological guidelines set forth by Churchill (1979) and Evrard et al. (2009). Data was collected from a total of 514 respondents across all research types. Based on this framework, we propose a new definition and a unidimensional scale that is both reliable and valid at exploratory and confirmatory levels. A five-items scale consisting of Likert type of five points ranging from strongly disagree to strongly agree.